2019
DOI: 10.3390/jcm8111996
|View full text |Cite
|
Sign up to set email alerts
|

Kambin’s Triangle Approach versus Traditional Safe Triangle Approach for Percutaneous Transforaminal Epidural Adhesiolysis Using an Inflatable Balloon Catheter: A Pilot Study

Abstract: Spinal stenosis is a common condition in elderly individuals. Many patients are unresponsive to the conventional treatment. If the transforaminal epidural block does not exert a sufficient treatment effect, percutaneous transforaminal epidural adhesiolysis (PTFA) through the safe-triangle approach using an inflatable balloon catheter can reduce the patients’ pain and improve their functional capacity. We aimed to evaluate the safety and efficacy of the Kambin’s-triangle approach for PTFA using an inflatable ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
12
1
Order By: Relevance
“…31 Gil HY et al, showed that kambin's triangle approach can be beneficial in patients where entry through safe triangle is difficult. 32 In our study, there was a single case of spinal nerve root pricking in the subpedicular approach whereas no pricking was reported in the Kambin's triangle approach but this difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 53%
“…31 Gil HY et al, showed that kambin's triangle approach can be beneficial in patients where entry through safe triangle is difficult. 32 In our study, there was a single case of spinal nerve root pricking in the subpedicular approach whereas no pricking was reported in the Kambin's triangle approach but this difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 53%
“…The sample size was calculated from a previous published study using WHO sample size calculator with power of study 80% and level of significance 5% (considering fall in NRS from 5.3 ± 1.89 to 4.0 ± 2.58) 10 , which came out to be 80.…”
Section: Methodsmentioning
confidence: 99%
“…The conventional target lies immediately below the 6 o'clock portion of the pedicle (Dog's eye), within the so-called safe triangle [59]. An alternative window for injection is the Kambin's triangle which adopts a lower location of injection within the intervertebral foramen and proved to be equivalent to the traditional safe triangle in efficacy [60]. Owing to its lower location within the neural foramen, it may be preferable to use Kambin's triangle for thoracolumbar injections to avoid injuring the artery of Adamkiewicz which almost invariably course within the upper and middle portions of the neural foramen, the injury of which can result in rare but devastating complications like paraplegia [61] (Fig.…”
Section: Guidance For Lumbar Foraminal Accessmentioning
confidence: 99%